A SOCIOLINGUISTIC ANALYSIS OF INDOGLISH USED ON INSTAGRAM CAPTIONS - Putri Kristanti, Ine; Seli, sastika; Fiani, Ani (Lingustic, Literature and English Education, 2024)
The aim of the study was to identify the types of Indoglish and to describe the factors of using Indoglish on Instagram captions. In this study, the researcher used a descriptive qualitative method and the data was collected through documentation and observation. The data were analyzed by using Farihah and Suhartono's study of types of English. The factors of using Indoglish were analyzed using Holmes's theory. The findings of this study indicate that 1) there were two types of Indoglish including a) Indonesian elements in foreign languages, namely phoneme appearance, word addition b) Foreign Elements in Indonesian, namely adoption, and translation with classification into several categories including; Indoglish language translation form of verbs category, Indoglish language translation form of nouns category, Indoglish language translation form of adjective category, Indoglish language translation form of adverbs category, Indoglish language translation forms phrase category 2 (two) words, and Indoglish language translation forms phrase category 3 (three) words, Indoglish language translation forms phrase category 4 (four) words, Indoglish language translation forms phrase category 5 (five) words, Indoglish language translation forms phrase category 6 (six) words, Indoglish language translation forms phrase category 7 (seven) words, Indoglish language translation forms of phrase category 8 (eight) words, Indoglish language translation forms of phrase category 9 (nine) words, Indoglish language translation forms of phrase category 10 (ten), Indoglish language translation forms of clause categories and Indoglish language translation forms of sentence categories. 2) The factors of using Indoglish in the Instagram caption by Indonesian female singers found there were four, namely the solidarity-social distance scale, the status scale, the formality scale, and the referential and affective function scale.